FORMATION OF THE STRESS-RELIEVED STRUCTURE IN THE WELDED REGION OF GAS TUNGSTEN-ARC-WELDED ARMOR STEEL WITH THE HELP OF HEAT DISTRIBUTION - Karaaslan, A.; Akca, C. (SPRINGER, 2009)
The structure and properties of welded joints of armor steel formed by gas tungsten arc welding (GTAW) are studied.
Keywords: armor steel; gas tungsten arc welding; microstructure; hardness; heat affected zone; welded joint; matrix metal; Metallurgy & Metallurgical Engineering